2007
DOI: 10.1024/1010-0652.21.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Arousal of Flow Experience in a Learning Setting and Its Effects on Exam Performance and Affect

Abstract: Abstract. Flow experience is associated with learning motivation, performance and positive affect. Therefore it is important to analyze its antecedents. An important antecedent for experiencing flow is the balance between the person's skill and how challenging the situation is (Csikszentmihalyi, 1990). According to Atkinson's (1957) risk-taking model, only individuals with high hope-of-success prefer situations in which a balance of challenge and skill is given while individuals with high fear-of-failure try t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 20 publications
3
72
0
5
Order By: Relevance
“…It furthermore predicted performance in a reaction task (Puca and Schmalt 1999;IMM: MMG) and correlated with response latencies in a Stroop task when stimuli were presented subliminally, but not, when presented supraliminary (Langens and Dorr 2006;IMM: MMG). The implicit achievement motive was associated with intrinsic motivation (Schüler 2007;IMM: MMG) and the implicit, but not the explicit achievement motive interacted with the corresponding basic need for competence (according to Self-Determination Theory, Deci and Ryan 1985) to predict intrinsic motivation and flow experience IMM: MMG). Components of the more differentiated OMT implicit achievement motive measure (pressure to achieve, coping with failure) predicted grades at university courses in stressful learning situations (Scheffer 2005; IMM: OMT).…”
Section: Implicit Motives and Their Differentiation From Explicit Motmentioning
confidence: 99%
See 2 more Smart Citations
“…It furthermore predicted performance in a reaction task (Puca and Schmalt 1999;IMM: MMG) and correlated with response latencies in a Stroop task when stimuli were presented subliminally, but not, when presented supraliminary (Langens and Dorr 2006;IMM: MMG). The implicit achievement motive was associated with intrinsic motivation (Schüler 2007;IMM: MMG) and the implicit, but not the explicit achievement motive interacted with the corresponding basic need for competence (according to Self-Determination Theory, Deci and Ryan 1985) to predict intrinsic motivation and flow experience IMM: MMG). Components of the more differentiated OMT implicit achievement motive measure (pressure to achieve, coping with failure) predicted grades at university courses in stressful learning situations (Scheffer 2005; IMM: OMT).…”
Section: Implicit Motives and Their Differentiation From Explicit Motmentioning
confidence: 99%
“…Gable (2006) found hope of affiliation to be related with less loneliness and fear of rejection as associated with more loneliness. Further studies showed that MMG motives moderate the relationship between challenge-skill-balance and flow experience (Schüler 2007) and moderate the effects of an emotional writing intervention on well-being (Langens and Schüler 2005). For further evidence for MMG validity see Langens and Schmalt (2009) and Sokolowski et al (2000).…”
Section: The Multi-motive Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…a state manifestation of the flow experience) are characterized by "an exclusive and intense concentration on the task at hand, where there is an absence of distraction, a perception of time being distorted, and where action and awareness merge in the performance of the activity" (p. 237). Research has shown flow to be positively related to positive performance, increased creativity, and higher well-being (Clark & Haworth, 1994;Csikszentmihalyi & LeFevre, 1989;Massimi & Carli, 1988;Shernoff, Csikszentmihalyi, Schneider, & Shernoff, 2003;Schüler, 2007). This has led to the conceptualization of flow being an 'optimal experience' for work and productivity (e.g., Fullagar & Kelloway, 2009;Nakamura & Csikszentmihalyi, 2002).…”
Section: Defining and Conceptualizing Flow And Flow-statesmentioning
confidence: 99%
“…However, given that the current body of literature, research directly investigating the differences of impact across workplace aggression constructs is somewhat limited, it will take a considerable effort before these boundaries are In addition, legislation for a healthy workplace has received much stronger support at the international level. Laws protecting workers from and addressing the impact of workplace aggression were passed in Sweden in 1994, Britain in 1997, France in 2001, Australia in 2005, Ireland in 2007, and in Canada in 2004, 2007. Given the expanded legal ramifications that workplace aggression has internationally, and the expanding U.S. legislation coverage underway, understanding what behaviors fall under the workplace aggression umbrella will be critical in creating, supporting, and enforcing workplace aggression policies.…”
Section: Practical Implicationsmentioning
confidence: 99%